ANALYSIS OF ETHICAL CONSISTENCY CHALLENGES AND THEIR ROLE IN THE SOCIAL CONDEMNATION OF ECO-TRAVELERS - Abdullayeva, Farangiz Otabekovna (THE INNOVATION ECONOMY, 2026)
This article analyzes the role of ethical consistency challenges in the phenomenon of social condemnation of eco-travelers. The study examines the conflicts between the high ethical goals set by eco-travelers and the practical constraints of real-life situations. Specifically, it explores how a single “ecological mistake” by a traveler can discredit their entire persona and trigger public backlash or social indignation. The research highlights the mechanisms of perceived ethical inconsistency and the subjective social perception involved in this process. The findings offer a deeper understanding of why ethical purity is demanded from eco-travelers and how its absence fuels social judgment.